2020
DOI: 10.5267/j.msl.2019.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Impact of strategic capabilities on organizational ambidexterity in the commercial banks in Jordan: The mediating role of knowledge management

Abstract: This study seeks to explain the impact of strategic capabilities on organizational ambidexterity, in the presence of knowledge management. The study population consists of managers of commercial banks in Jordan. The sample included (200) respondents by distributing the study questionnaires to them, where the returned questionnaires and valid to statistical analysis were (168). Structural equation modelling (SEM) was used as an inferential statistical analysis technique to test the hypotheses of the study. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…Additionally, the current study found that there is a positive effect of task significance on Organizational ambidexterity. This result is consistent with the study of (Abazeed, 2020;Abuziad, 2020;Johari &Yahya, 2009). This result explains that task significance is very important especially if the task has an impact on the employee's lives (Anjum et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, the current study found that there is a positive effect of task significance on Organizational ambidexterity. This result is consistent with the study of (Abazeed, 2020;Abuziad, 2020;Johari &Yahya, 2009). This result explains that task significance is very important especially if the task has an impact on the employee's lives (Anjum et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…The results of the current study found that there is a positive effect of the Job Characteristics Model (skills variety, task identity, task significance, autonomy, and feedback) on organizational ambidexterity. This result is aligned with studies of (Abazeed, 2020;Abuziad, 2020;Ketabchi;. We might be explaining this result by the role of job characteristics on organizational ambidexterity because if the employees have known their task very well, they will perform their task effectively and efficiently which lead to an ambidextrous organization.…”
Section: Discussionsupporting
confidence: 86%
“…Kori et al, (2020) also suggest that strategic internal factors enhances competitive advantage which is of utmost importance to enable a company to meet customer wants and needs effectively. Strategic internal factors in an organization is continuing to be an area that is receiving increased awareness, both in theory and practice especially in the banking industry (Abazeed, 2020) as the only option available for the industry to succeed in today's competitive business environment.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Stahapit (2021) observes that the environment always posed certain requirements which forced the organization to come Journal of International Business and Management (JIBM) https://rpajournals.com/jibm up with efficiency and innovation in its operations in order for it to survive and prosper. According to Abazeed (2020),this ultimately led the firm's management to adopt a strategy for the firm which somehow reflected the environment and at the same time was part of a managerial statement of the firm's objectives given the comparative advantage of the firm and that was competitive advantage of a bank. Huda et al, (2020) explains in that theory that when managers made decisions concerning competitiveness of bank ,they always considered all aspects of the existing situation and took action on those aspects that was crucial to the circumstances at hand.…”
Section: Research Objectivesmentioning
confidence: 99%
See 1 more Smart Citation